Why is "early childhood intensive care" an Italian association of neonatology study group? - Nicola Pozzi; Gabriella D'Angelo; Eloisa Gitto; Gruppo di Studio Terapia Intensiva della Prima Infanzia della SIN (BMC, 2019)
Abstract To date, a large number of children are hospitalized inappropriately in adult intensive care units, where the minimum standards of care are not applied to young patients. It is well-known that the child is not a small adult. Recently it has been demonstrated that critically ill children hospitalized in pediatric intensive care receive higher quality of care, and have better outcomes, besides a lower mortality rate, compared to those admitted to adult intensive care units. We believe that the management of the critically ill child is an area of expertise of the neonatologist, who however must acquire specific skills and abilities of pediatric intensive medicine. The new idea of care is to offer in general hospitals 'broader' Neonatal Intensive Care Units, extended to infants and children in early childhood, based on territorial macro-areas and/or population of competence.